THE SURGICAL TREATMENT EFFECTIVENESS OF PATIENTS WITH MIDDLE EAR CANCER - P. V. Svetitskiy; M. A. Engibaryan; P. N. Meshceryakov (Южно-Российский онкологический журнал, 2020)
Among human malignant tumors, middle ear cancer is rare: up to 0.06%, and among ear tumors — up to 5%. Due to the late detection of the tumor, patients turn to a specialist with advanced, nearly or completely unresectable disease, and it limits the treatment to conservative one with poor results. Combination treatment is the most effective option, where surgery plays a leading role. During surgery, temporal bone tissues affected by a tumor are removed. Over the decade from 2003 to 2018, we operated on 10 patients with advanced cancer of the middle ear who had pre‑ viously received radiation therapy (cumulative dose 40 Gy). Lymphadenectomy was first performed in 3 patients with neck metastases. During surgery, the temporal bone was removed in all patients. The results of treatment demonstrated that relapse‑free survival in 3 patients was 2 years, in 4 patients — 3, in 2 patients — 4 years; 1 patient — no data available. Two patients who survived 3 years received repeated surgery due to recurrence. Upon discharge, patients underwent chemotherapy at the place of residence. A clinical case of a 42‑years old patient with advanced disease is presented. Cranial spiral x‑ray computed tomography showed advanced middle ear cancer affecting cranial bones. The patients underwent radical surgery on the temporal bones with isolation of the facial nerve and exposure of the jugular bulb. Histological examination of tumor tissues of the external auditory canal and parotid salivary gland confirmed squamous cell carcinoma. Temporal bone tissues affected by the tumor were removed during surgery. The elements of the organ of corti and cochlea were exposed and preserved: the horizontal semicircular canal, the oval and round windows. A wide external auditory canal was formed, and the wound was packed; skin grafting was performed. The patient has been in remission for 8 months.